IDENTIFIKASI POTENSI KONFLIK TENURIAL DI WILAYAH KESATUAN PENGELOLAAN HUTAN PRODUKSI (KPHP) MODEL UNIT VI GORONTALO - Asri, .; Golar, .; Racman, Imran (Jurnal Warta Rimba, 2018)
Bumela is a village which located in Bilato Sub-District of Gorontalo District which directly adjacent to Limited Production Forest Area and Protected Forest in Forest Management Unit Production (FMUP) VI Gorontalo. Urgent needs of people living around the area, mainly plantation land, agricultural land for cultivation as well as settlement as a residence for the community lead to illegal use of forest areas or land tenure, land cover change occured. The purpose of this study to find out the potential tenure conflict in Forest Management Unit Production (FMUP) VI Gorontalo. This study was conducted for two months are April until May 2016. Location of the study is the area of production forest at FMUP Model VI Gorontalo, Bumela village, Bilato Sub-District, Gorontalo District. Data collection was accomplished in four ways: (1) Literature study, (2) In-depth Interview, (3) Field observation, (4) Group discussion. The study indicated that (1) Potential of tenurial conflict in FMUP Model unit VI Gorontalo has a diffrerent perception and interpretation which held between the parties on their rights of land and forest resources, low of intensity of security and protection management, uncertainty of forect tenure and resources; (2) Potential of dominant tenurial conflict is the low of management intensity, security and protection.Keywords: Potential Conflict, Tenure Conflict, FMU